APPLICATION OF WEIGHT PRODUCT AND TOPSIS METHODS IN SELECTING THE BEST ONLINE TRANSPORTATION SERVICE - Nur Fitriani; Hamidah Nasution; Ismail Husein; Hashem Beg, Abul (Pena Cendekia Insani, 2025)
This study emphasises the application of mathematical and computational modelling to support multi-criteria decision-making in the selection of online transportation services. Using Microsoft Excel, the research employs the Weighted Product (WP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods to assess alternatives based on six quantitative criteria: price, promotion, service variety, payment method, convenience, and punctuality. The integrated application of WP and TOPSIS provides a systematic process of normalisation, weighting, and ranking to determine the optimal alternative. The findings indicate that GOJEK achieves the highest preference value (0.6107), followed by GRAB (0.5533), IN-DRIVE (0.5000), and MAXIM (0.3893). The methodological contribution of this research lies in demonstrating how the integration of WP and TOPSIS within computational tools establishes an effective mathematical framework for optimising decision-making in service evaluation.